ChemInform Abstract: Chiral Integrated Catalysts Composed of Bifunctional Thiourea and Arylboronic Acid: Asymmetric Aza‐Michael Addition of α, β‐Unsaturated Carboxylic Acids. Issue 45 (October 2016) - Hayama, Noboru; Azuma, Takumi; Kobayashi, Yusuke; Takemoto, Yoshiji
Abstract: A range of enantioenriched β‐(benzyloxy)amino acid derivatives are prepared in high yields and with high enantioselectivities.